1997
DOI: 10.1002/bjs.1800841120
|View full text |Cite
|
Sign up to set email alerts
|

Pathological appearance of the stomach after endoscopic mucosal resection for early gastric cancer

Abstract: Gastric carcinomas to be resected by EMR should be smaller, especially if located in the body or cardia. Accurate diagnosis of the width and depth of invasion is indispensable before proceeding to EMR. Surgery may be the treatment of choice when there is submucosal invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 6 publications
3
21
0
Order By: Relevance
“…In addition, EMR can be associated with a high recurrence rate, particularly with larger lesions that lead to incomplete resection. 1,2 In contrast to EMR, the technique of endoscopic submucosal dissection (ESD) allows en bloc resection of even large lesions (Ͼ2 cm). ESD of well-defined selected cases of early gastric cancer was recently accepted as an alternative to surgery in Japan.…”
mentioning
confidence: 99%
“…In addition, EMR can be associated with a high recurrence rate, particularly with larger lesions that lead to incomplete resection. 1,2 In contrast to EMR, the technique of endoscopic submucosal dissection (ESD) allows en bloc resection of even large lesions (Ͼ2 cm). ESD of well-defined selected cases of early gastric cancer was recently accepted as an alternative to surgery in Japan.…”
mentioning
confidence: 99%
“…They also found lymph node metastases in 10.3% (4/39) of the latter group. Korenaga et al 18 reported the pathologic results of 11 patients who underwent gastrectomy after incomplete EMR. They confirmed residual tumor in 4 of 5 patients with a positive resection margin, and in 3 of 6 with submucosal invasion, one of whom had lymph node metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…16 The risks of residual tumor or lymph node metastases after incomplete EMR have been discussed in previous reports. 17,18 In this study, we analyzed 19 patients who underwent EMR followed by successive surgical resection for a positive resection margin or submucosal invasion, to evaluate the role of surgery after incomplete EMR for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Tani have reported a difference of 2 to 5 mm between the edges diagnosed by macroscopic and microscopic features of the resected specimens. Korenaga et al 24 have shown that it is technically difficult to obtain a sufficient margin of resected specimen by EMR for cancer located on the upper or middle third of the stomach. In our study, the number of fragments in EMR was larger in the noncurative group, and cancer cells remained only in the mucosal layer adjacent to the EMR scar in most surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been few reports regarding additional treatment for residual cancer after EMR. 12,24 Korenaga et al 24 have recommended gastrectomy with lymph node dissection for the treatment of residual cancer after EMR because of the risk of lymph node metastasis. Our previous study reported that laparoscopic surgery is feasible for the treatment of residual cancer after EMR because of the overall curability and some additional advantages, including decreased pain, rapid return of gastrointestinal function, and a reduction in pulmonary dysfunction.…”
Section: Discussionmentioning
confidence: 99%